DESAIN PERKUATAN GEOTEXTILE PADA TIMBUNAN KHUSUS STUDI KASUS JALAN TOL RUAS PEKANBARU PADANG SEKSI BANGKINANG PANGKALAN STA 1+035 IC - Afrilia, Missi; Junaidi, Junaidi (Jurnal TeKLA, 2023)
The bearing capacity of a soil is the ability of a soil to safely withstand the stresses placed on it without causing shear collapse and excessive settlement. The lack of bearing capacity of the subgrade at the location causes two problems, namely due to the height of the embankment reaching 10 m, it will cause landslides and collapse of the bearing capacity of the subgrade. This paper aims to determine how many safety factors occur manually and using the XSTABLE application and how many layers of geotextile are needed. From the results of analysis and calculation obtained (SF) that occurs without reinforcement is 0.701 (soil without load), 0.688 (soil plus structural load), 0.694 (soil plus truck load), 0.624 (soil plus earthquake load), and 0.548 (soil plus all loads). The maximum embankment height that can be done without reinforcement is 2.51 m high with SF 1.5 and the number of geotextile layers required is if the geotextile specification used is woven type 100 - 50 with Sv 0.2 m, there are 46 layers with layers 1-34 using 2 sheets of geotextile. As for the specification of geotextile woven 200 - 50 with Sv 0.25, there are 32 layers with layers 1-5 using 2 sheets of geotextile and Sv 0.4m 25 layers with layers 1-17 using 2 sheets of geotextile.